3D Automated Breast Volume Sonography : A Practical Guide - Gazhonova, Veronika (Springer International Publishing : Imprint: Springer, 2017)
This book introduces an exciting new method for breast ultrasound diagnostics - automated whole-breast volume scanning (3D ABVS). Scanning technique is described in detail, with guidance on scanning positions and protocols. Imaging findings are then illustrated and discussed for normal breast variants, the different forms of breast cancer, fibroadenomas, cystic disease, benign and malignant male breast disorders, mastitis, breast implants, and postoperative breast scars. In order to aid appreciation of the benefits of 3D ABVS, comparisons with findings on X-ray mammography and conventional 2D hand-held US are presented. Readers will be especially impressed by the convincing demonstration of the advantages of the new method for diagnosis of breast cancer in women with dense glandular tissue. In enabling readers to learn how to perform and interpret 3D ABVS, this book will be of great value for all who are embarking on its use. It will also serve as a welcome reference for radiologists, oncologists, and ultrasonographers who already have some familiarity with the technique.
Keywords: Medicine.; Gynecology.; Radiology.; Oncology.; elektronické knihy; electronic books